Penerapan Model Project Based Learning untuk Meningkatkan Kreativitas dan Prestasi Belajar Materi Bangun Datar - Timbul Sasongko (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The aim of the research is to increase the application of the PjBL model in increasing the creativity and learning achievement of Flat-Round Mathematics for Class IV Semester II Students at SD Negeri 6 Punung for the 2022/2023 Academic Year. This research is a type of classroom action research. The research subjects were 5 students in Class IV of SD Negeri 6 Punung. Data collection: observation, questionnaires, tests, and documentation. Creative success is at least